Recipient splenic artery utilization for arterial re-anastomosis in living donor liver transplantation: Single-center experience - DEMİRBAŞ, BAHA TOLGA (My University, 2012)
Thrombosis of recipient hepatic artery is a life threatening complication for liver transplantation. The etiology of hepatic arterial thrombosis is multi-factorial and can be caused by intimal dissection, poor surgical technique and coagulopathies. The patency of hepatic arterial flow is very important for both graft survival and patient survival. Intraoperative diagnosis of inadequate hepatic arterial flow found with Doppler ultrasonography is essential in order to achieve good results after liver transplantation. Urgent re-anastomosis is necessary when the arterial blood flow is insufficient. We performed 317 living donor liver transplantations from July 2004 to July 2011. We used recipient splenic artery for hepatic artery reconstruction in six patients. These six patients were included in this study. Using the recipient splenic artery is a simple, safe and practical alternative for hepatic artery re-anastomosis in living donor liver transplantations.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Surgery Medicine Sciences; GASTROENTEROLOJİ VE HEPATOLOJİ; Klinik Tıp; Klinik Tıp (MED); CERRAHİ; GASTROENTEROLOGY & HEPATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); SURGERY; Surgery; Gastroenterology; Hepatology; Living donor; Liver Transplantation; Splenic Artery; HEPATIC-ARTERY; RECONSTRUCTION; REVASCULARIZATION; COMPLICATIONS; GRAFT